Apparent Digestibility of Feed Nutrients, Total Tract and Ileal Amino Acids of Broiler Chicken Fed Quality Protein Maize (Obatampa) and Normal Maize - Onimisi, P.A.; Dafwang, I.I.; Omage, J.J.; Onyibe, J.E. (International Journal of Poultry Science, 2008)
Two hundred and forty Ross Broiler chicken were used in a completely randomized design to evaluate the apparent digestibility of Obatampa, a quality protein maize (QPM) and normal maize (NM) nutrients with respect to crude protein, crude fibre, ether extract, ash and nitrogen free extract, as well as total tract and Ileal amino acids. There were 4 dietary treatments, each having 3 replicates with 20 birds per replicate. Two pure diets each of NM and QPM were formulated, one each without synthetic lysine supplementation (T2 and T3 for NM and QPM respectively) and one each with synthetic lysine supplementation (T2 and T4 for NM and QPM respectively). The diets were fed to the birds for two weeks before feacal collections and dissecting for Ileal sampling. Apparent Digestibility of nutrients, fecal and Ileal amino acids were higher for normal maize diets without lysine supplementation. Supplementation of diets with synthetic lysine increased nutrient and amino acids digestibility for QPM.